2012
DOI: 10.1517/13543784.2012.704020
|View full text |Cite
|
Sign up to set email alerts
|

Targeting memory processes with drugs to prevent or cure PTSD

Abstract: Introduction Post-traumatic stress disorder (PTSD) is a chronic debilitating psychiatric disorder resulting from exposure to a severe traumatic stressor and an area of great unmet medical need. Advances in pharmacological treatments beyond the currently approved SSRIs are needed. Areas covered Background on PTSD, as well as the neurobiology of stress responding and fear conditioning, is provided. Clinical and preclinical data for investigational agents with diverse pharmacological mechanisms are summarized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 198 publications
(147 reference statements)
0
23
0
Order By: Relevance
“…Pavlovian conditioning contributes to disorders like PTSD (Rau and Fanselow 2009;Cain et al 2012;Mahan and Ressler 2012). Using this task, we have found that NE enhances memory by acting during learning.…”
Section: Discussionmentioning
confidence: 96%
“…Pavlovian conditioning contributes to disorders like PTSD (Rau and Fanselow 2009;Cain et al 2012;Mahan and Ressler 2012). Using this task, we have found that NE enhances memory by acting during learning.…”
Section: Discussionmentioning
confidence: 96%
“…Of note, such a response mimics a feature of posttraumatic stress disorder (Jovanovic et al 2009), which in turn has also been associated with excessive noradrenergic functioning (Pitman 1989;O'Donnell et al 2004). Moreover, patients suffering from this anxiety disorder may present impairment in traumatic memory extinction (Cain et al 2012). Interestingly, extinction impairments were also demonstrated in healthy humans after enhancing noradrenergic activity with yohimbine during aversive memory consolidation (Soeter and Kindt 2012), and in rats after activating b-adrenergic receptors in the amygdala during fear memory reconsolidation (Debiec et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…By contrast, the fear response would be attenuated after longer reactivation of the original fear memory owing to its gradual suppression by the extinction memory, which could also be facilitated by yohimbine. Of note, based on its facilitating effects on fear extinction, this drug has been suggested as a potential pharmacological adjuvant to exposurebased psychotherapies for posttraumatic stress disorder (Cain et al 2004(Cain et al , 2012, but see Holmes and Quirk 2010). In view of current findings, however, this approach should be reconsidered since it could backfire, potentiating reconsolidation rather than extinction of traumatic memories.…”
Section: Discussionmentioning
confidence: 99%
“…53 Interventions can be costly, time consuming, and not necessary in all cases. If those at greatest risk can be identified and offered a brief intervention commencing before the memory is fully consolidated, 54,55 the risk of that exposure may be mitigated. It is important to note that in this pilot trial a large percentage of patients seen in the emergency department were ineligible for enrollment, 56 and that 65%–70% were seen at the 12-week follow-up, which is less than the 70%–80% follow-up rates that have been seen in some other acute medical injury PTSD intervention trials.…”
Section: Discussionmentioning
confidence: 99%